2017
DOI: 10.1038/srep45084
|View full text |Cite
|
Sign up to set email alerts
|

A role of the SAM domain in EphA2 receptor activation

Abstract: Among the 20 subfamilies of protein receptor tyrosine kinases (RTKs), Eph receptors are unique in possessing a sterile alpha motif (SAM domain) at their C-terminal ends. However, the functions of SAM domains in Eph receptors remain elusive. Here we report on a combined cell biology and quantitative fluorescence study to investigate the role of the SAM domain in EphA2 function. We observed elevated tyrosine autophosphorylation levels upon deletion of the EphA2 SAM domain (EphA2ΔS) in DU145 and PC3 prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
2
48
1
Order By: Relevance
“…Relevant to this, the truncation of the SAM domain induced autophosphorylation in the activation loop of EphA2 in cells [29,32], whereas the truncation of the SAM domain in EphA3 exhibited decreased activation loop autophosphorylation [31], suggesting an intramolecular regulatory role of the Eph SAM domain. The increased receptor clustering and phosphorylation observed upon deletion of the SAM domain on EphA2 and EphB2 dimerisation [28][29][30] seems to be counter-intuitive as the SAM domain is a known dimerisation domain predicted to favour Eph receptor dimerisation/oligomerisation. One possibility to reconcile this discrepancy is that the SAM domain may impose steric hindrance on the kinase domain and the kinase domain could also be a major intracellular dimerisation determinant.…”
Section: Pbm Intracellularlymentioning
confidence: 74%
See 3 more Smart Citations
“…Relevant to this, the truncation of the SAM domain induced autophosphorylation in the activation loop of EphA2 in cells [29,32], whereas the truncation of the SAM domain in EphA3 exhibited decreased activation loop autophosphorylation [31], suggesting an intramolecular regulatory role of the Eph SAM domain. The increased receptor clustering and phosphorylation observed upon deletion of the SAM domain on EphA2 and EphB2 dimerisation [28][29][30] seems to be counter-intuitive as the SAM domain is a known dimerisation domain predicted to favour Eph receptor dimerisation/oligomerisation. One possibility to reconcile this discrepancy is that the SAM domain may impose steric hindrance on the kinase domain and the kinase domain could also be a major intracellular dimerisation determinant.…”
Section: Pbm Intracellularlymentioning
confidence: 74%
“…Truncation of the SAM domain was shown to promote EphA2 and EphB2 homo-dimerisation and clustering at the plasma membrane, respectively [28][29][30], although opposing findings suggested that the presence of the SAM domain enhanced EphA3 dimerisation in cells [31]. Relevant to this, the truncation of the SAM domain induced autophosphorylation in the activation loop of EphA2 in cells [29,32], whereas the truncation of the SAM domain in EphA3 exhibited decreased activation loop autophosphorylation [31], suggesting an intramolecular regulatory role of the Eph SAM domain. The increased receptor clustering and phosphorylation observed upon deletion of the SAM domain on EphA2 and EphB2 dimerisation [28][29][30] seems to be counter-intuitive as the SAM domain is a known dimerisation domain predicted to favour Eph receptor dimerisation/oligomerisation.…”
Section: Pbm Intracellularlymentioning
confidence: 99%
See 2 more Smart Citations
“…Ligand binding causes a clustering of the Eph receptors, leading to the opening of an activation loop, and a subsequent tyrosine phosphorylation (shown in green) of the kinase domain. SAM domain offers a docking surface for downstream signaling and is reported to be involved in receptor oligomerization (Shi et al, 2017). RBD, Receptor-Binding Domain; LBD, Ligand-Binding Domain; CRD, Cysteine-Rich Domain; FN, Fibronectin III domain; Y-P, Phospho-Tyrosine; SAM, Sterile Alpha Motif.…”
Section: Figurementioning
confidence: 99%